Concept inventory test on cellular respiration for senior high school students: An assessment of reliability and validity - John Daryl C. Bace; Shaina D. Guiral; Nichelle Karla C. Galicia; Mark Jay Reyes; Sylvester Cortes (JPBI (Jurnal Pendidikan Biologi Indonesia))
Given the complexity of cellular respiration, there is a significant need for effective assessment tools that can accurately gauge students’ understanding, identify misconceptions, and provide educators with actionable insights to improve instruction. Concept Inventory Test (CIT) has emerged as a valuable instrument in science education for this purpose. The aim of this study is to develop a Concept Inventory Test on cellular respiration and assess its reliability and validity. This study employed a mixed-method sequential exploratory approach for each assessment. The study was conducted in a private school in Cebu, targeting the senior high school students. The results of the study showed that the developed Concept Inventory Test’s reliability and validity are made apparent by the process used to gather supporting data, as well as by the findings and observations. Furthermore, this Concept Inventory Test serves a significant instrument for classroom assessment, promotes additional research on students’ critical comprehension, and shows how these diagnostic inventories link to the students’ competencies. However, a greater number of respondents should be taken to account to observe the consistency of the Concept Inventory Test results.